The Effect of Compensation and Motivation on Employee Satisfaction and Performance at PT Pasma Karya Indonesia - Abbas, Ronny; Astuty, Pudji (Journal Research of Social Science, Economics, and Management, 2023)
Basic performance is necessary to maintain employees with a decent standard of living, but compensation also provides a tangible measure of an individual’s value to the company. Human resource management according to the author is a protest to regulate existing human resources within an organization so that it is effective and efficient and is carried out through existing functions to achieve sales, employee, and community goals. the authors use an error tolerance limit of 5%, the population used in this study are employees of PT. Pasma Karya Indonesia. The HR Division, namely the HRD Section, totaled 100 people. The results of the study show that compensation, motivation have positive and significant direct effect on job satisfaction and employee performance.